1995
DOI: 10.1063/1.469002
|View full text |Cite
|
Sign up to set email alerts
|

Application of pair correlation theory to positronium compounds

Abstract: Extension of weak orthogonality ͑WO͒ techniques developed by Szalewicz et al. and coupled pair equations derived by Jeziorski et al. to positronium compounds are presented. These methods enable us to calculate many-electronic positronium compounds with explicitly correlated functions. These methods were applied to positronium hydride ͑PsH͒ with Hylleraas-type functions ͑HTF's͒, and the total energies, the positron-electron two-photon annihilation rates, and the positronium binding energies were calculated. Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…We have employed the HF and the truncated singly and doubly excited configuration interaction (CISD) levels, where three types of excitations, single electronic, single positronic and both single electronic-single positronic excitation configurations are included. We note here that our CISD level of calculation includes no pure electronic correlation contributions (no double electronic excitation terms) [16,22,26]. Strictly speaking, further extension of the configuration space and the polarized basis functions will definitely improve the total energy and properties, since the CI expansion for positronic systems is known to converge slowly.…”
Section: Numerical Calculationsmentioning
confidence: 95%
See 1 more Smart Citation
“…We have employed the HF and the truncated singly and doubly excited configuration interaction (CISD) levels, where three types of excitations, single electronic, single positronic and both single electronic-single positronic excitation configurations are included. We note here that our CISD level of calculation includes no pure electronic correlation contributions (no double electronic excitation terms) [16,22,26]. Strictly speaking, further extension of the configuration space and the polarized basis functions will definitely improve the total energy and properties, since the CI expansion for positronic systems is known to converge slowly.…”
Section: Numerical Calculationsmentioning
confidence: 95%
“…In order to investigate positronic compounds with a theoretical approach, it is necessary to develop a computational method that treats both electron and positron (multi-components) on an equal footing quantum mechanically. There have been some theoretical attempts to investigate a possible formation of positron-bound states based on mean-field [10][11][12][13], manybody perturbation [14,15], configuration interaction (CI) [16][17][18][19][20][21][22][23][24][25][26], variational calculations using explicitly correlated Gaussian (ECG) wave functions [27][28][29] and quantum Monte Carlo (QMC) [30][31][32][33][34][35][36] techniques. Most calculations have shown that molecules with strong dipole moments (>3-4 Debye) can indeed bind a positron.…”
Section: Introductionmentioning
confidence: 99%
“…For analyzing the properties of the positronic molecular complexes, it is desirable to use the theoretical methodology taking account of the contribution of electron-positron correlation such as many-body perturbation, [23,24] configuration interaction (CI), [25][26][27] variational calculations using explicitly correlated Gaussian wave functions, [28][29][30] and the ab initio quantum Monte Carlo method, [31][32][33][34] rather than the Hartree-Fock (HF) method. [35][36][37][38] Due to the limitation of our computational resource, however, we used the HF level of the multicomponent molecular orbital (MC_MO) method, and qualitatively discuss the characteristic features of the positron binding to aspartame conformers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, at the HF level of MC_MO theory,22, 23 electronic and positronic molecular orbitals of a positron‐binding molecule are obtained by solving both the electronic and the positronic Roothaan equations simultaneously. Although some post‐HF techniques, such as the many‐body perturbation theory (MBPT),26, 27 the configuration interaction (CI) method,28, 29 the ab initio quantum Monte Carlo (QMC) method,30, 31 and variational calculations using explicitly correlated Gaussian (ECG) wave functions,32 are available in the theoretical scheme, we employed the HF level of the MC_MO method to discuss the PA of the nucleic base molecules and the spatial distribution of bound positrons qualitatively. As seen in our previous theoretical work on positronic alkali metal hydrides,31 HF calculations give reasonable PA values for a qualitative discussion.…”
Section: Methodsmentioning
confidence: 99%